L’arbre à Tunis : hypothèses pour une histoire de l’espace public - Myriam Bennour-Azooz; Pierre Donadieu; Taoufik Bettaieb (Projets de Paysage)
The tree is part of the urban landscape. It is fully "rooted" in the context of the city life. But unlike other aspects that underpin the urban landscape, the tree, as it is perceived ; with its own symbols and meanings, belongs to the sensitive human world. The changing story of Tunis’ urban landscape of was experienced through its trees and their arrangement. This is the main hypothesis of this thesis. Before colonization, the Medina had few trees in public spaces, where the spatial organization drew its roots in the Sharia (Divine Law), and the first precept of them was the respect for families’ privacy. In this sense, the streets remained narrow and poorly maintained. But the trees were sometimes included among the dwellings ; in the patios : locations for private and family life. The most often found essences were those mentioned in the Koran for their virtues, mainly citrus and aromatic species (the precepts of divine law used to be obeyed even when it concerned the interiors’organization).Then in the late nineteenth century, during the protectorate, the city expanded beyond the walls. Wide avenues lined with rows of trees, new species sometimes trimmed, emerged. The European city opened up to trees and the Tunisois began to discover another urban world imported from Europe. With the Independence (in 1956), the capital, swollen by the rural exodus, spread. On one hand, the wealthy Tunisians, wanting access to the modern living, inhabited neighborhood which combined new European-style (large imposing avenue trees) and Tunisian traditions (large garden planted with citrus and aromatic species). On the other hand, Tunisians fleeing the country and a difficult life in search of better incomes have appropriated adjacent spaces to the capital and have reproduced, as far as possible, their rural way of life.